EVALUASI PENGGUNAAN GOOGLE CLASSROOM DENGAN METODE END USER COMPUTING SATISFACTION (EUCS) - Muhammad Fatkhur Rizal; Ahmad Heru Mujianto; Ginanjar Setyo Permadi, (Prosiding Seminar Nasional Sains, Teknologi, Ekonomi, Pendidikan dan Keagamaan (SAINSTEKNOPAK), 2023)
Abstract In this study, an evaluation was carried out on the LMS Google Classroom which has been used as an online learning medium, especially at the Faculty of Information Technology, Hasyim Asy'ari University during Covid-19. The impact of the covid-19 pandemic has led to online learning activities. This aims to keep the learning process running even during the Covid-19 pandemic. The evaluation used in the Google Classroom LMS uses the EUCS method which has five dimensions in its measurement including Content, Accuracy, Format, Ease of Use, and Timelines. The results of this study were obtained from data analysis on evaluating the use of the Google Classroom LMS using the EUCS method, which was 82.79%, with the assessment criteria being "Good". Keywords: learning, google classroom, EUCS Abstrak Dalam penelitian ini dilakukan evaluasi pada LMS Google Classroom yang telah digunakan sebagai media pembelajaran daring khususnya di Fakultas Teknologi Informasi Universitas Hasyim Asy’ari selama covid-19. Dampak dari pandemic covid-19 menyebabkan kegiatan pembelajaran daring. Hal ini bertujuan agar proses pembelajaran tetap berjalan meskipun dalam pandemi covid-19. Evaluasi yang digunakan pada LMS Google Classroom menggunakan metode EUCS yang memiliki lima dimensi dalam pengukurannya meliputi Content, Accuracy, Format, Ease of Use, dan Timelines. Hasil penelitian ini yaitu diperoleh analisis data pada evaluasi penggunaan LMS Google Classroom menggunakan metode EUCS yaitu sebesar 82,79%, dengan kriteria penilaian yaitu “Baik”. Kata kunci: pembelajaran, google classroom, EUCS